2018
DOI: 10.1044/2018_jslhr-l-17-0402
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Synchrony of Multimodal Communication in Early Language Development

Abstract: https://doi.org/10.23641/asha.6912242.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 45 publications
2
20
0
6
Order By: Relevance
“…For example, two studies have shown that the degree to which 12-month-old infants use integrated and simultaneous pointing–speech combinations predicts their later language development. The ability to selectively use this multimodal communicative strategy to successfully initiate and maintain joint attention at 12 months is related to language development at 18 months (Igualada et al, 2015; for similar findings see Murillo et al, 2018).…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…For example, two studies have shown that the degree to which 12-month-old infants use integrated and simultaneous pointing–speech combinations predicts their later language development. The ability to selectively use this multimodal communicative strategy to successfully initiate and maintain joint attention at 12 months is related to language development at 18 months (Igualada et al, 2015; for similar findings see Murillo et al, 2018).…”
Section: Discussionmentioning
confidence: 78%
“…Later in development, the same predictive pattern arises. A recent study investigated the changes in the temporal synchrony between gesture and speech of multimodal communicative behaviors in the crucial transition from babbling to two-word productions (Murillo et al, 2018). It found that, at 15 months, the proportion of overlap between gestural and vocal elements, and the proportion of gesture strokes overlapping with vocalizations, were both related to lexical development 3 months later.…”
Section: Developmental Evidence That Gesture and Prosody Are Precursomentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the previous studies focused on oral or written language skills, while we studied prelinguistic skills. Prelinguistic and linguistic skills are closely related ( Cadime et al, 2017 ; Lohmander et al, 2017 ; Murillo et al, 2018 ; Paavola et al, 2005 ), but it is quite possible that different ERPs are associated with the level and development of prelinguistic as compared to linguistic skills. The investigations that best compare to our study in terms of the behavioral outcomes, assessed associations between ERPs and neurodevelopmental level in prematurely born children ( Fellman et al, 2004 ; Maitre et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Many fundamental principles of human communication, such as intentionality and the engagement in joint attention, are learned during the prelinguistic phase ( Feldman, 2007 ; Tomasello et al, 2007 ; Watt et al, 2006 ), and prelinguistic skills are associated with later language skills ( Cadime et al, 2017 ; Lohmander et al, 2017 ; Määttä et al, 2016 ; Murillo et al, 2018 ; Paavola et al, 2005 ). Although both efficient neural auditory processing and good prelinguistic skills are vital for early communicative development ( Kuhl, 2010 ; Snowling and Melby-Lervåg, 2016 ), only two studies have, to our knowledge, investigated their associations ( Fellman et al, 2004 ; Maitre et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%